Vertical velocity patterns over India and neighbourhood during break monsoon an active monsoon periods - DATTA , R. K.; MUKERJI, T. K. (MAUSAM, 1975)
Vertical velocity patterns at different levels of the atmosphere, over India and neighbouring areas have been obtained for a situation each of active and break monsoon. A five layer quasi-geostrophic model has been developed for the above computations. These vertical velocity patterns are discussed to bring out their salient features and their differences. A model for the vertical velocity field for active/break monsoon has also been proposed.